Resting membrane potential and Na+,K+-ATPase of rat fast and slow muscles during modeling of hypogravity - Tyapkina, O; Volkov, E; Nurullin, L; Shenkman, B; Kozlovskaya, I; Nikolsky, E; Vyskočil, František (Physiological research, 2009)
Antiorthostatic hindlimb suspension (unloading) decreased the resting membrane potential (RMP) of skeletal muscle fibers in fast extensor digitorum longus (EDL) and slow soleus (SOL) muscle of the rat by about 10 % within 7 days and more. Inactivation of the membrane Na+, K+-pump by ouabain brought about similar depolarization as unloading. The increased sodium permeability of the membrane was excluded as the major cause of this depolarization by experiments in which TRIS was substituted for Na+ in the medium. On the other hand, the decrease in the electrogenic participation of the Na+,K+-pump is apparently one of the causes of RMP decrease during hypogravity, in EDL muscle in particular.
Keywords: Weightlessness Simulation; svalová kontrakce; Muscle Contraction; simulace stavu beztíže; financování organizované; krysa rodu Rattus; Financing, Organized; zvířata; potkani Wistar; sodíko-draslíková ATPasa; kosterní svaly; Rats, Wistar; Male; Muscle, Skeletal; Rats; Sodium-Potassium-Exchanging ATPase; Animals; Membrane Potentials; mužské pohlaví; membránové potenciály